New insights into the relationship between airway inflammation and asthma. - Wardlaw, A; Brightling, C; Green, R; Woltmann, G; Bradding, P; Pavord, I (2002)
Asthma is a condition characterized by variable airflow obstruction, airway hyper-responsiveness (AHR) and airway inflammation which is usually, but not invariably, eosinophilic. Current thoughts on the pathogenesis of asthma are focused on the idea that it is caused by an inappropriate response of the specific immune system to harmless antigens, particularly allergens such as cat dander and house dust mite, that result in Th2-mediated chronic inflammation. However, the relationship between inflammation and asthma is complex, with no good correlation between the severity of inflammation, at least as measured by the number of eosinophils, and the severity of asthma. In addition, there are a number of conditions, such as eosinophilic bronchitis and allergic rhinitis, in which there is a Th2-mediated inflammatory response, but no asthma, as measured by variable airflow obstruction or AHR. Bronchoconstriction can also occur without obvious airway inflammation, and neutrophilic inflammation can in some cases be associated with asthma. When we compared the immunopathology of eosinophilic bronchitis and asthma, the only difference we observed was that, in asthma, the airway smooth muscle (ASM) was infiltrated by mast cells, suggesting that airway obstruction and AHR are due to an ASM mast cell myositis. This observation emphasizes that the features that characterize asthma, as opposed to bronchitis, are due to abnormalities in smooth muscle responsiveness, which could be intrinsic or acquired, and that inflammation is only relevant in that it leads to these abnormalities. It also emphasizes the importance of micro-localization as an organizing principle in physiological responses to airway inflammation. Thus, if inflammation is localized to the epithelium and lamina propria, then the symptoms of bronchitis (cough and mucus hypersecretion) result, and it is only if the ASM is involved -- for reasons that remain to be established -- that asthma occurs.